Impacto e incidencia del evento el niño sobre la población urbana y rural del cantón Babahoyo durante el período 2023-2024. - Ibarra Taco, Jenny Aracely (2025)
This study analyzes the impact and incidence of the El Niño phenomenon on the urban and rural population of the Babahoyo canton during the period 2023-2024. This climatic phenomenon, characterized by the anomalous warming of the Pacific Ocean, has generated adverse effects in Ecuador, especially in the province of Los Ríos, causing floods, river overflows and damage to infrastructure, homes and educational units. The main objective of the research is to evaluate the effects of the El Niño event in Babahoyo, identifying the most vulnerable areas and analyzing the response of risk management agencies. To do this, a mixed research approach was used, combining qualitative and quantitative methods, including surveys, documentary analysis and field observation. The results show a high level of vulnerability in various areas of the canton, as well as deficiencies in emergency planning and response by the responsible agencies. Based on these findings, mitigation and adaptation strategies are proposed to strengthen community resilience and improve institutional response capacity to future El Niño events. This study seeks to provide key information for decision-making by authorities and contribute to the formulation of public policies focused on disaster risk management in Babahoyo. Keywords: El Niño event, vulnerability, risk, mitigation strategies.